Seven names for the bellbird : conservation geography in Honduras - Bonta, Mark, 1969- (Texas A & M University Press, 2003)
Annotation "Seven Names for the Bellbird showcases the deep-rooted local traditions of bird appreciation and holds them up as a model for sound management of the environment. Through his recounting of local lore, author Mark Bonta makes the interaction between culture and avifauna in Latin America a key to better understanding the practice of biodiversity protection. He offers a significant contribution to the scarce anthropological and geographical literature on human-environment relationships in Central America and also provides wonderful stories of native birds and their human observers." "Bonta uses the concept of 'conservation geography' - the study of human beings and their landscapes, with natural resource conservation in the forefront - to advance his argument. He describes many cases in which local individuals and their traditional knowledge of birds contribute to a de facto variety of bird conservation that precedes or parallels 'official' bird protection efforts." "This book is not offered as 'proof' that all birds have happy futures in the Neotropics. Bonta recognizes the ravages of both human pressures and natural disasters on the birds and forests. But he shows that in many instances, birds are safe and even thrive in the presence of local people, who 'celebrate them just as often as they persecute them.'"--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved